Fire shut up in my bones : a memoir - Blow, Charles M., 1970- (Houghton Mifflin Harcourt, 2014)
A respected journalist describes the abuse he suffered at the hands of a close family relative, the effect this had on his formative years and how he overcame the anger and self-doubt it left behind.